Penglihatan Stereo Dalam Pengukuran Jarak - Kassim, Muhammad Hafiz (Universiti Sains Malaysia, 2006)
Human with complex vision system can extract information about depth and positional relationship between different elements of an image. It can be done automatically by combining the image from left eye and right eye, then forming a three dimensional images. Moreover, human also can extract useful information from images such as the changing size of familiar elements, vanishing lines, shadows and the changing intensity of textures. The operation of human vision became the basic technique on designing a number of range detection techniques such as binocular vision system or stereo vision system. If two images from the same object are formed (stereo images), the relative range or depths of the different points from the image plane can be extracted by comparing the two images. Range detection using stereo images requires two operations. Firstly, the point pairs in the two images are determined which is correspond to the same points at the object that been measured. It will give the disparity value of the point pair. Then, the range or location of the point on the object are determined using triangular techniques. So, using that operations, the algorithm for measuring of stereo images can be made and give the measured value needed. Finally, this measurement system can measured in good condition for the distance range from 0.4m to 1.2m using the stereo vision system.